Shelters in the Night. The Role of Architecture in the Process of Understanding High-Altitude Areas - Roberto Dini; Stefano Girodo (Revue de Géographie Alpine)
The design and construction of huts in the Western Alps, which developed from the late eighteenth century and throughout the nineteenth, constitutes a key step in the process of discovery and cultural appropriation of the mountains. The installation of stable shelters offering overnight accommodation at high altitudes, superseding the precarious bivouac-style campsites, makes it possible to carry out wide-ranging scientific, alpine and geographic explorations there for the first time. Such shelters act as catalysts in the transformation of the alpine region from an ancestral space to an outpost of scientific knowledge, the “playground” of mountaineers, a place of symbolic and political conquest and, successively, a site of loisir for tourists.In just a few decades, mountain guides and mountaineering associations played a decisive role in this process, initiating the progressive physical alteration of high-altitude areas and paving the way for a widespread building and infrastructural colonisation that has been constantly evolving to this day.Structurally, mountain huts and bivouacs reflect the ways in which the space, landscape and time have been conceptualised and used over the ages, forming an interesting area of study: from the early structures, which were self-contained and impervious to the surrounding landscape, serving merely to provide protection from the outside, up to today’s landmark structures.